2004
DOI: 10.1177/154405910408301s16
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOdent: An Optical Method for Caries Detection

Abstract: The onset of caries is characterized by demineralization of dental hard tissues. Optimal fluoridation with respective oral hygiene habits and diet may stop the progression of a lesion and even allow for its remineralization. The aim of modern dentistry must be a preventive approach rather than invasive repair of the disease. This is possible only with early detection and respective preventive measures. Some of today's diagnostic tools are not sensitive enough to detect this early onset of destruction. Tools ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
174
1
30

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(209 citation statements)
references
References 16 publications
4
174
1
30
Order By: Relevance
“…with the progression of caries (7,13). In the present study, significant differences were observed between the Diagnodent readings for caries in enamel and dentin, with higher values of fluorescence related to dentin.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…with the progression of caries (7,13). In the present study, significant differences were observed between the Diagnodent readings for caries in enamel and dentin, with higher values of fluorescence related to dentin.…”
Section: Discussionmentioning
confidence: 55%
“…In the 1990's, good perspectives on the use of laser fluorescence for the diagnosis of caries were presented and this technology was proven able of detecting early demineralization, especially when a fluorescent dye is added to the mineralized surface (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] The device emits a red laser beam at a wavelength of 655 nm (1 mW maximum power) and measures the lesion's fluorescence (at 720-750 nm), produced by microbial metabolic products, the porphyrins. 14 Although the device functions with the same principle as the old one, its main difference is at the tip, which is rotatable around its long axis to facilitate use in approximal areas. A laser light is sent to the tooth through a single sapphire fiber tip, which at the same time collects the reflected light and filters the ambient and the fluorescent light entering the tip.…”
Section: Introductionmentioning
confidence: 99%
“…They also allow monitoring of lesions over time. This ability is of great importance in the field of ultra-conservative dentistry because it enables dentists to quantitatively identify progressing lesions, which is impossible with conventional tools [17].…”
Section: Discussionmentioning
confidence: 99%